Compendium of key human rights documents of the African Union - Sixth Edition - Magnus Killander (Pretoria University Law Press (PULP), 2016)
This is the sixth edition of the Compendium of key human rights documents of the African Union updated to August 2016. This compendium contains documents on human rights adopted under the auspices of the African Union (AU) and its predecessor, the Organization of African Unity (OAU), including documents adopted by the African Commission on Human and Peoples' Rights, the African Court on Human and Peoples' Rights and the African Committee on the Rights and Welfare of the Child. Due to space constraints only extracts are reprinted of many of the documents. This compendium is by no means comprehensive but includes some key documents of relevance for students of the African human rights system and others interested in its functioning. Extracts from documents related to the New Partnership for Africa's Development (NEPAD) and the African Peer Review Mechanism (APRM) reprinted in previous editions of this compendium have been left out of this edition. For comprehensive coverage of human rights law in Africa, see www.chr.up.ac.za and the web sites listed at the end of this compendium. The assistance of Frans Viljoen and Lizette Hermann in preparing this edition of the compendium and the financial support of the Norwegian government for its printing is gratefully acknowledged. About the editors: Christof Heyns is Director, Institute for International and Comparative Law in Africa, University of Pretoria. Magnus Killander is a researcher at the Centre for Human Rights, University of Pretoria and is also the co-editor of African Human Rights Law Reports.